A pilot study on ethnic variations and reverse sexual dimorphism in permanent teeth dimensions of sub-adult Santhal population of India (Bulletin of the International Association for Paleodontology, 2024)
The teeth are resistant towards environmental and decomposition processes and can often be found in cases of mass disasters, charred or mutilated bodies. India is a land of diverse ethnicities and odontometric data of specific tribal populations is deficient. The Santhals are one of the largest tribal groups of India and exploring their dental traits will be useful in deciphering their biological profile, oral health and dietary patterns. The present study aims to explore sexual dimorphism in the tooth dimensions of sub-adult Santhal population and study their ethnic variations with other tribal population groups. A cross-sectional study was conducted on 100 participants (50M/ 50F) aged between 14-20 years of the Santhal origin. Direct measurements of 14 variables were taken intra-orally using digital vernier callipers. All the data was statistically analysed using SPSS.21.00. The mandibular canines showed the highest classification accuracy (MnRC=85%, MnLC=87%) in univariate discriminant function analysis. The mandibular left canine showed a sexing accuracy of 82.5% in the ROC Analysis. The maxillary and mandibular canine width of the Santhal females were smaller than those of the other north-eastern tribal groups. A statistically significant difference (p